Trust and distrust corruption in office in Britain and its empire, 1600-1850 - Knights, Mark 1950- (Oxford scholarship online, 2021)
Mark Knights offers an overview of Britain's history of corruption in office in the pre-modern era between 1600 and 1850. Drawing on extensive archival material, Knights shows how corruption in the domestic and imperial spheres interacted, and how the concept of corruption developed during this period, changing British ideas of trust and distrust